The Neuro-Mechanical Processes That Underlie Goal-Directed Medio-Lateral APA during Gait Initiation - Honeine, Jean-Louis; Schieppati, Marco; Crisafulli, Oscar; Do, Manh-Cuong (Frontiers in Human Neuroscience, 2016)
Gait initiation involves passing from bipedal to unipedal stance. It requires a rapid movement of the center of foot pressure (CoP) towards the future swing foot and of the center of mass (CoM) in the direction of the stance foot prior to the incoming step. This anticipatory postural adjustment (APA) allows disengaging the swing leg from the ground and establishing favorable conditions for stepping. This study aimed to describe the neuro-mechanical process that underlies the goal-directed medio-lateral APA. We hypothesized that controlled knee flexion of the stance leg contributes to the initial medio-lateral (ML) displacement of the CoP and to the calibration of the first step. Nine subjects initiated gait starting from three different initial stance widths of 15 cm (Small), 30 cm (Medium), and 45 cm (Large). Optoelectronic, force platform and EMG measurements were performed. During APA, soleus activity diminished bilaterally, while tibialis anterior activity increased, more so in the stance leg than in the swing leg, and to a larger extent with increasing initial stance width. Knee flexion of the stance leg was observed during APA and correlated with the ML CoP displacement towards the swing leg. ML CoP and CoM displacements during APA increased with increasing stance width. The activity of stance-leg tibialis anterior was correlated with the degree of knee flexion. Swing-leg tensor fasciae latae was also active during APA. Across subjects, when stance-leg tibialis activity was low, tensor fasciae latae activity was large and vice versa. The modulation of the ML CoP position during APA allowed the gravity-driven torque to place the CoM just lateral to the stance foot during step execution. Accordingly, the gravity-driven torque, the ML CoM velocity during step execution, and the step width at foot contact were lower in the Small and greater in the Large condition. Consequently, the position of the stepping foot at foot contact remained close to the sagittal plane in all three conditions. Conclusively, coordinated activation of hip abductors and ankle dorsiflexors during APA displaces the CoP towards the swing leg, and sets the contact position for the swing foot.